Intracranial dural arteriovenous fistula mistaken as cervical transverse myelitis. Issue 3 (5th December 2018) - Peethambar, Gowri A; Whittam, Daniel H; Huda, Saif; Alusi, Sundus; Puthuran, Mani; Chandran, Arun; Eldridge, Paul R; Jacob, Anu
Abstract : We describe a man with an intracranial dural arteriovenous fistula that presented as a subacute longitudinally extensive cervical myelopathy. The uncommon location of the fistula and the absence of specific radiological signs resulted in initial misdiagnosis as longitudinally extensive transverse myelitis. Neurologists should have a high index of suspicion for dural arteriovenous fistula in older men, especially those with subacute or chronic symptoms, acellular cerebrospinal fluid and, particularly, if there is neurological deterioration soon after corticosteroid treatment. Patients need early angiography to identify this treatable cause of myelopathy.